Personalisation - An Emergent Institutional Logic in Healthcare?; Comment on "(Re) Making the Procrustean Bed? Standardization and Customization as Competing Logics in Healthcare" - Ewan Ferlie (Kerman University of Medical Sciences, 2018)
This commentary on the recent think piece by Mannion and Exworthy reviews their core arguments, highlighting their suggestion that recent forces for personalization have emerged which may counterbalance the strong standardization wave which has been evident in many healthcare settings and systems over the last two decades. These forces for personalization can take very different forms. The commentary explores the authors' suggestion that these themes can be fruitfully examined theoretically through an institutional logics (ILs) literature, which has recently been applied by some scholars to healthcare settings. This commentary outlines key premises of that theoretical tradition. Finally, the commentary makes suggestions for taking this IL influenced research agenda further, along with some issues to be addressed.